Pedagogical conditions of the health savings competence in the structure of the professional training for the future social pedagogues - Tatiana Kostyuchenko (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
he article highlights the main aspects of the health savings competence as a necessary component in the structure of professional training for the future social workers. The conditions in general and pedagogical conditions, particularly for the successful implementation of the health savings expertise in the training for future specialists of the social-pedagogical sphere. The study highlighted the following main pedagogical conditions: the formation of positive motivation to the health savings competence, using various types of motor activity, propaganda of the healthy lifestyle, focused and effective organization in time for work and leisure.